Estratégias em competição para indefinir o agente em textos jornalísticos: um olhar para as formas pronominais - Oliveira, Gaylha Wégila de (2023)
In this dissertation we are going to present some strategies in competition to make indetermined the subject in Brazilian Portuguese, specifically from Paraíba (PB), in special the indeterminacy from pronominal forms, analyzing written language data from two genres - the interview and the article. Thus, based on a functionalist theoretical perspective, we seek to answer the following question: Are the forms of indeterminacy of the agent subject in PB presenting innovative uses and undergoing behavioral changes in the written language? In this sense, starting from the hypothesis that there are new configurations in the occurrences of representation of pronominal subjects, as a objective, in general, we aim to analyze the functioning of the personal pronouns mentioned as alternative ways of indetermining the subject in texts of the journalistic area. As a corpus, we used a sample of 24 interviews and 24 articles in two Brazilian magazines: VEJA and CLAUDIA. The time frame of the selected texts comprises the years between 2020 and 2022. The choice of these magazines was motivated by the fact that they are periodicals with a large circulation and because they have stylistic characteristics that are very different from each other. In order to create a comparison between traditional and functionalist approaches to language, we rely on authors such as: Cunha e Cintra (2009), Bechara (2010), Rocha Lima (2011), Neves (2000), Castilho (2010) e Bagno (2011). In addition, studies such as those by Duarte (1993, 2007) and Lopes (2008) were fundamental in understanding the data analyzed. From the observation of the data, we infer that new forms are being used as a strategy of indeterminacy of the subject, among them: você (you), o a gente (we), o nós (we) (express or null). Furthermore, it was possible to observe changes in the understanding of the uses of SE (if). We conclude, therefore, that the language is changeable, and the uses do not always match what is prescribed in the grammars.